Treatment patterns in anticoagulant therapy in patients with newly diagnosed atrial fibrillation in Belgium: results from the GARFIELD-AF registry. Issue 4 (4th July 2019) - Cools, Frank; Wollaert, Bart; Vervoort, Geert; Verstraete, Stefan; Voet, Joeri; Hermans, Kurt; Heyse, Alex; De Wolf, Axel; Hollanders, Geert; Boussy, Tim; Anné, Wim; Vercammen, Jan; et al.
Abstract: Background: AF, anticoagulation, NOACs, changing patterns of prescription. Methods: We describe baseline data and treatment patterns of patients recruited in Belgium in the Global Anticoagulant Registry in the FIELD-Atrial Fibrillation (GARFIELD-AF). Recruitment began when novel oral anticoagulants (NOACs) were introduced and provides a unique picture of changing treatment patterns over time. 1713 patients with a new (≤6 weeks duration) diagnosis of non-valvular atrial fibrillation (NVAF) and at least one investigator-defined stroke risk factor were recruited between May 2012 and August 2016, and will be prospectively followed for at least 2 years. Results: Overall, anticoagulant use in Belgium was higher than in the rest of Europe: 80.1% of patients received an anticoagulant ± antiplatelet (AP) therapy (14.5% on vitamin K antagonists; 65.6% on NOAC), 10.7% AP therapy and 9.3% no antithrombotic therapy. Over time, we observed an increase in anticoagulant use and a decrease in AP use for stroke prevention. NOAC use in Belgium was the highest of Europe at the study start, with many countries catching up later. In high stroke risk patients (CHA2 DS2 -VASc ≥2), anticoagulants were used in 84.3%, leaving 15.7% unprotected. In low risk patients (CHA2 DS2 -VASc 0-1) anticoagulants were overused (58.7%). Factor Xa inhibitors were used more frequently than direct thrombin inhibitors. Conclusion: Guideline adherence on stroke prevention was higher in Belgium than in the rest of Europe, and increased over time. NOAC use in Belgium was the highest of Europe at the study start, with many countries catching up later. Possible reasons are discussed. Clinical Trial Registration: http://www.clinicaltrials.gov . Unique identifier: NCT01090362.